2018
DOI: 10.3347/kjp.2018.56.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin: In-Vivo Synergy with Metronidazole as Anti-Blastocystis Therapy

Abstract: Blastocystis is an enteric Straminopile in tropical, subtropical and developing countries. Metronidazole has been a chemotheraputic for blastocystosis. Failures in its regimens were reported and necessitate new studies searching for alternative therapeutic agents. Aim of current study is to investigate potential effects of Atorvastatin (AVA) compared to the conventional chemotherapeutic MTZ in experimentally Blastocystis-infected mice. Anti-Blastocystis efficacy of AVA was evaluated parasitologically, histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
7
0
3
Order By: Relevance
“…MTZ gave an acceptable effect with moderate Blastocystis cysts count reduction, moderate improvement of histopathological inflammatory changes and the immunological response. This was in accordance with the results of Basyoni et al (2018) 2014) reported complete failure of MTZ and reported that it should no longer be considered the recommended treatment for Blastocystis infection. Also, Batista et al (2017) found inadequate response to MTZ and their systematic review showed greatly variable responses to MTZ treatment ranging from 0% to 100.…”
Section: Introductionsupporting
confidence: 92%
“…MTZ gave an acceptable effect with moderate Blastocystis cysts count reduction, moderate improvement of histopathological inflammatory changes and the immunological response. This was in accordance with the results of Basyoni et al (2018) 2014) reported complete failure of MTZ and reported that it should no longer be considered the recommended treatment for Blastocystis infection. Also, Batista et al (2017) found inadequate response to MTZ and their systematic review showed greatly variable responses to MTZ treatment ranging from 0% to 100.…”
Section: Introductionsupporting
confidence: 92%
“…It was shown that the most widely used MVA pathway inhibitors for clinical applications, namely, mevastatin (also known as compactin or ML-236B) and mevinolin, affected trophozoite growth, an effect that could be reversed by the addition of mevalonate in the culture medium [106]. Even Blastocystis , Acanthamoeba and some apicomplexan parasites, including Toxoplasma , Cryptosporidium and Plasmodium , showed susceptibility to statins and apparent enzymatic capacity to metabolize MVA in protein extracts [76,77,84,107,108,109].…”
Section: Biosynthesis Of Aromatic and Isoprenic Precursors Of Prenmentioning
confidence: 99%
“…First of all, it was previously demonstrated that G. lamblia is sensitive to the statins mevastatin and mevinolin, two classical inhibitors of the MVA pathway and for consequence the isoprenic precursors synthesis [69,106]. In the case of Blastocystis , Acanthamoeba and some apicomplexan parasites, including Toxoplasma , Cryptosporidium and Plasmodium , it was demonstrated the susceptibility to several other statins and there is an evidence of enzymatic capacity to metabolize MVA in P. falciparum extracts [77,81,84,106,107,108]. Curiously, there is no evidence for pathways responsible for isoprenic chain biosynthesis in E. histolytica .…”
Section: Summary Of Drug Targets Related To Prenylquinone Biosynthmentioning
confidence: 99%
“…debido a que este parásito afecta la integridad de la barrera epitelial del intestino, aumentando la permeabilidad por reorganización del epitelio de unión intestinal a través de la fosforilación de la cadena ligera de miosiona mediada por la Rho quinasa (ROCK); esto porque las estatinas protegen la integridad de la barrera epitelial por inhibición de ROCK, HMG-CoA reductasa y la cisteína proteasa. Específicamente de las estatinas como coadyuvante en el tratamiento de blastocistosis se han probado la atorvastatina y la lovastatina 39,49,50 .…”
Section: Tratamiento De La Blastocistosisunclassified